Dynamic Shifts in Tracheal Tube Cuff Pressure: Impact of Ventilation Modes, Patient Positioning, and Duration in ICU Settings- A Prospective Observational Study - Rana, Rajswee; Pandith, Vaishnavi; Agarwal, Ankit; Jain, Gaurav (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: In intensive care unit (ICU), various factors like patient positioning, duration of tracheal intubation and modes of mechanical ventilation can significantly affect endotracheal tube cuff pressures. Failure to maintain optimal cuff pressure may result in various complications. This study aims to evaluate the effect of these factors on cuff pressure. Methods: A prospective observational study was conducted in the ICU of a tertiary care hospital. Adult patients intubated with a cuffed endotracheal tube for mechanical ventilation were enrolled. The cuff pressure measurements were taken at four time points: T1- in controlled ventilation in supine position; T2- after two hours in controlled ventilation and in supine position; T3- in controlled mode immediately after transitioning to a propped-up position from supine position and T4- in spontaneous mode in a propped-up position. Results: The mean cuff pressure at T1 was 25.34 cm H2O (SD 3.75, 95% CI 24.06-26.62), at T2 was 21.66 cm of H2O (SD 3.40, 95% CI 20.49-22.83), at T3 was 20.03 cm H2O (SD 3.30, 95% CI 18.89-21.16) and at T4 was 15.17 cm H2O (SD 4.24, 95% CI 13.71-16.63). Mean cuff pressures were found to significantly vary with time, change in position and mode of ventilation. It was highest during controlled ventilation in supine position, which progressively decreased at the end of two hours, after keeping the patient in propped up position and furthermore during spontaneous ventilation. Conclusion: Ventilation mode, patient positioning, and the duration of mechanical ventilation significantly affect tracheal tube cuff pressure in ICU patients.